Evaluation of the barrier and antimicrobial properties of biodegradable films based on potato waste starch containing natural additives - Apaza Cusiatau, Christian Ricardo (2024)
This study investigates the antimicrobial and water vapor barrier properties of biodegradable films made from potato (Solanum tuberosum) waste starch and the natural additives glycerol, propolis, and montmorillonite ("chaco"). Films were produced using the casting method, and their physical, antimicrobial, and barrier properties were analyzed. Film compositions were established using an experimental design of mixtures. The water vapor permeability values ranged from 0.44 × 10−10 to 8.55 × 10−10 g/(m·s·Pa). The permeation energy was lower than that of polyvinyl chloride and polypropylene films but higher than that of cellophane films. The solubility values ranged from 58 to 66%, and the tensile modulus ranged from 2.15 to 5.15 MPa. The largest inhibition halo diameter obtained for Staphylococcus aureus was 17 mm. The developed packages completely biodegrade within 30 days under composting conditions at ambient temperatures. These findings suggest the potential application of these biodegradable packages for fresh products such as fruits and vegetables.